Comparative study of the chemical properties and composition of the Mentha Pulegium L. of Algerian origin and that of Tunisian origin - Mondher Barhoumi (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
The aim of this study was to compare the chemical composition, antioxidant, antifungal and antileishmanial activities of the essential oils that were obtained from Mentha pulegium L. cultivated both in Algeria and in Tunisia. The kinetics of antioxidant activity was also studied. The essential oils are obtained by steam distillation with a yield of 1.30 and analyzed by gas chromatography coupled to mass spectrometry (GC/MS) where 30 compounds were identified. The Antioxidant activity was defined using the scavenging test of free radicals (DPPH), while ascorbic acid is used as positive control. The values of IC50 are between 95-107 µg.mL-1. The results obtained by the study of the antifungal activity, show that the essential oils of the Algerian and Tunisian mentha pulegium have significant antifungal activity. The antileishmanial activity was tested against Leishmania Major and Donovani (LV9) axenic amastigotes. The IC50 values evaluated in L. major promastigote and axenic amastigote forms were in the range of 100 µg.mL-1.